Everyday heroes - Johnson, Beth 1956- (Marlton, NJ Townsend Press, 2003)
Profiles twenty young men and women of a variety of ethnic backgrounds whose courage and determination have helped them overcome such obstacles as poverty, racism, abuse, neglect, illness, and drugs.
CSSP-6324, CSSP-6325 donated by The Rotary Club of Beaverton, Oregon, United States of America.
Keywords: Biography -- 20th century; Heroes -- Biography; Women heroes -- Biography; Heroes -- Biography -- Juvenile literature; Women heroes -- Biography -- Juvenile literature; Biography -- 20th century -- Juvenile literature